2021
DOI: 10.3390/cells10071576
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Femoral Veins in Deep Vein Thrombosis in a Porcine Model

Abstract: Deep vein thrombosis (DVT) is a severe disease affecting the human venous system, accompanied by high morbidity and mortality rates caused by early and late complications. The study aimed at analyzing the changes in the transcriptome of the femoral vein caused by DVT in the porcine model based on the formation of the thrombus in vivo. The study was performed on 11 castrated male pigs: a thrombus was formed in each left femoral vein in six animals; the remaining five served as a control group. Total RNA was iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…The precise roles of each vascular and immune cell population in thrombus formation, resolution, and post-thrombotic vein wall remodeling are incompletely understood. Studies using bulk RNA sequencing to examine early transcriptomic changes in the vein wall across murine 12 and porcine 13 models of DVT have been performed. However, the molecular signature of DVT within the vein wall at single-cell resolution is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The precise roles of each vascular and immune cell population in thrombus formation, resolution, and post-thrombotic vein wall remodeling are incompletely understood. Studies using bulk RNA sequencing to examine early transcriptomic changes in the vein wall across murine 12 and porcine 13 models of DVT have been performed. However, the molecular signature of DVT within the vein wall at single-cell resolution is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The current research, which aimed at analyzing the changes in the transcriptome of PA with induced PE, is the continuation of our previous studies devoted to the transcriptomic profiling of femoral veins in DVT. We mainly disclosed that dysregulation of TNF, NF-κB, and apoptosis pathways affect inflammatory responses and the formation, remodeling, and resolution of thrombus in the course of DVT [ 16 ]. Whilst, the present project not only uncovered the genetic biomarkers of PE but also unrevealed that the disturbed homeostasis in the biosynthesis of proteins in the ER plays a major role in the pathogenesis of PE.…”
Section: Discussionmentioning
confidence: 99%
“…A previous analysis of the changes in the transcriptome of the femoral vein caused by DVT in the porcine model based on the formation of the thrombus in vivo, disclosed that TNF, NF-κB and apoptosis pathways are strongly dysregulated during the thrombus formation [ 16 ]. The present study also revealed genes with significant allelic imbalance involved in the TNFα signaling pathway, such as the Coiled-coil domain containing 3 (CCDC3), Thy-1 Cell Surface Antigen (Thy1) and TRAF2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, patients with breast cancer after resection may experience severe postoperative complications (8)(9)(10)(11). One of the most threatening complications is deep vein thrombosis (DVT), a severe disease in the venous system, which is a vital cause of high mortality of breast cancer (10,12,13).…”
Section: Introductionmentioning
confidence: 99%